2013
DOI: 10.1097/scs.0b013e318285d474
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Large Palatal Defect Using a Tongue Flap

Abstract: The aim of this study is to report the effectiveness of a tongue flap for covering a large hard and soft tissue defect following cleft of the palate. A young patient diagnosed with acute lymphoblastic leukemia underwent a surgical reconstruction of the cleft palate by Le Fort I osteotomy and palatal closure utilizing a tongue flap. The flap provided sound and lasting closure after the surgery, and the patient successfully healed. Our goal is to present this unique case and highlight how postoperative results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[2]. In that study, a 13-year-old patient with leukemia underwent the successful closure of a large palatal fistula using a tongue flap [6]. In a prospective study of 20 patients with anterior palatal fistulae (larger than 5 mm), Sodhi et al [7], reported that successful closure was achieved in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2]. In that study, a 13-year-old patient with leukemia underwent the successful closure of a large palatal fistula using a tongue flap [6]. In a prospective study of 20 patients with anterior palatal fistulae (larger than 5 mm), Sodhi et al [7], reported that successful closure was achieved in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, tongue flaps are still used and have their indication as dorsal, ventral, or lateral flaps. All require secondary surgery to free the pedicle, which can be avoided using free flaps. Also up to four weeks of feeding, swallowing and speaking with a fixed tongue and general reduction of patient life quality during this stage is a significant disadvantage of the tongue flap.…”
Section: Discussionmentioning
confidence: 99%
“…The study was retrospective and, therefore, did not require approval from the ethics committee. The medical charts were reviewed to obtain the following data: (1) age, (2) sex, (3) localization, (4) comorbidities, (5) medical treatment, (6) surgical resection, (7) flap type, and (8) time from debridement surgery to reconstruction.…”
Section: Methodsmentioning
confidence: 99%